Propos féminins sur le travail (1860-1933) - Danièle Bussy Genevois (Mélanges de la Casa de Velázquez, 2010)
This article presents points of discussion on female labour in Spain from the Sexenio until the Second Republic, sourced on women’s own declarations (conferences, news articles, association by-laws). The focus is thus not on labour from an economic standpoint but from an emancipatory, feminist and social perspective. These documents bear witness to the construction of an individual and a collective identity, and to advances in the professional sphere that research into political citizenship tends to ignore.